Multiculturalism in the city: managing diversity - Laura Capel (European Regional Science Association (ERSA), 2003)
The issue of multiculturalism questions two essential elements that have conformed occidental society in the last two centuries: the nation-state and the citizenship. The former one, because multiculturalism questions the homogeneity in which is based, the later because the principle of individual equality is challenged by claims for the recognition of identities based on groups. We think that this issue is especially relevant at urban level. At the beginning of the XXI century, cities are where diversity is mainly concentrated, and were most conflicts based on multiculturalism arise, creating a rich diversity of social, cultural, religious traditions. Cities as Rotterdam or Brussels are examples of places were the diversity is already common, but other cities as Barcelona are only recently facing this phenomenon. Nation is what defines citizenship but there are other dimensions equally important in order to understand it and take changes into account. The local level is one of these dimensions, where the conflict between community and citizenship, universality and difference are more evident. In this paper we will analyse these issues. In first place we will analyse how theories of multiculturalism are applied to the local level, how the issue is identified from the urban sociology and the solutions proposed. As will be shown, we need to address to the concept of liberal citizenship. Later on we analyse models of citizen's participation that try to reflect the diversity of multiculturalism, concretely the model of deliberative and aggregate democracy. Multiculturalism refers to different phenomena, but this paper focus in the migration issue, because it is a paradigmatic example of the problems that multiculturalism arises. Moreover, is in cities were most of the immigration in European countries concentrates, which is the dimension we want to study.
Keywords: 330